2007
DOI: 10.1007/s00227-007-0703-3
|View full text |Cite
|
Sign up to set email alerts
|

Toxic dinoflagellates (Alexandrium fundyense and A. catenella) have minimal apparent effects on oyster hemocytes

Abstract: The possible effect of Alexandrium spp. containing paralytic shellfish poisoning (PSP) toxins on the hemocyte parameters of oysters was tested experimentally. In separate experiments, eastern oysters, Crassostrea virginica, were exposed to bloom concentrations of the sympatric dinoflagellate, Alexandrium fundyense, alone and in a mixture with a non-toxic diatom, Thalassiosira weissflogii, and Pacific oysters, Crassostrea gigas, were exposed to a mixed suspension of the sympatric, toxic species Alexandrium cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 22 publications
7
51
1
Order By: Relevance
“…These results are consistent with the findings of Hégaret et al (2007b), who demonstrated combined effects of P. olseni and the harmful-alga Karenia selliformis on concentration of circulating hemocytes and hemocyte phagocytic activity in Manila clams. Indeed, when quahogs were subjected to both stressors, combined infection with QPX and exposure to the HAB, hemocyte size decreased, indicating an increase in impact when both stressors were combined.…”
Section: Histological Features P-valuesupporting
confidence: 93%
“…These results are consistent with the findings of Hégaret et al (2007b), who demonstrated combined effects of P. olseni and the harmful-alga Karenia selliformis on concentration of circulating hemocytes and hemocyte phagocytic activity in Manila clams. Indeed, when quahogs were subjected to both stressors, combined infection with QPX and exposure to the HAB, hemocyte size decreased, indicating an increase in impact when both stressors were combined.…”
Section: Histological Features P-valuesupporting
confidence: 93%
“…Similarly, no effects of in vivo exposure to toxic Alexandrium spp. on hemocytes were found in oysters Crassostrea virginica and C. gigas, although they attained only low toxicities (<130 µg STXeq 100 g -1 ) (Hégaret et al 2007b). In the present study, in which R. philippinarum attained much higher toxicities, a significant, deleterious effect of A. tamarense on hemocyte function was found only for percent phagocytosis (15% reduction, p ≤ 0.05) and phagocytic capacity (11% reduction, p ≤ 0.01).…”
Section: Effects Of Psts On Manila Clam Hemocytescontrasting
confidence: 70%
“…cells or both. These in vitro exposures also revealed an intermediate reaction of haemocytes to K. mikimotoi, compared to K. selliformis, which was previously observed in vivo (Hégaret et al 2007a). Jenkinson and Arzul (2000) also showed intermediate haemolytic properties in K. mikimotoi, compared to K. selliformis, in exposures of horse red blood cells.…”
Section: Effect Of Harmful Algal Cells On Bivalve Haemocytes and Theisupporting
confidence: 51%